The Contribution Of Pesantren Culture To The Development Of Islamic Education Management System In The Modern Era - Albariki, Fahim; Anwar, M. Ali Misbakhul; Rohman, Maskuri Abdul (Sekolah Tinggi Agama Islam Al-Muntahy, 2024)
This research seeks to explore the role of pesantren culture in shaping Islamic education management systems that align with the needs of the modern world. The primary goal of the study is to understand how core pesantren values-such as solidarity, independence, discipline, and sincerity-can be integrated with contemporary management practices. The research adopts a qualitative approach, utilizing case studies, in-depth interviews, and observations at several well-established pesantren across Indonesia. The findings suggest that pesantren can preserve Islamic traditions while incorporating management innovations, particularly in areas like leadership, human resource management, finance, and the educational process. This study proposes that reinforcing a management framework rooted in pesantren culture can boost the effectiveness and sustainability of Islamic educational institutions in today’s era. The study highlights the importance of enhancing managerial training within pesantren, incorporating technology into teaching and learning, and improving financial management through more transparent and accountable systems. Furthermore, the research recommends future studies to investigate the implementation of pesantren-based management models in diverse pesantren types and to examine the influence of human resource capacity on the adoption of professional management practices.